Development of Interactive Multimedia for Introducing Letters and Numbers to Kindergarten Students - Saputra, Hendra Nelva; Said, Hasmira; Sarpina (Jurnal Smart Paud, 2024)
The aim of this research is to develop interactive multimedia for introducing letters and numbers that can be used in the learning process in kindergartens. This study uses the 4D development model, which includes the stages of define, design, develop, and disseminate. The data collection techniques used in this research are observation and questionnaires. The data analysis was conducted using Likert scale measurements. Overall, the developed interactive learning media has undergone a series of feasibility tests from various aspects, both by media experts and content experts. According to the media experts' assessment, this media obtained an average percentage of 91.67%, which falls into the "very feasible" category. This indicates that the media, both visually and functionally, meets the expected standards in educational media development. Additionally, the validation carried out by content experts, who evaluated aspects such as curriculum, material, evaluation questions, language, design, animation, and ease of use, resulted in an average percentage of 77.23%, categorized as feasible. This learning media is considered sufficiently effective and appropriate for use in the context of kindergarten education.